PO 79 - SÍNDROME DA IMPLANTAÇÃO DO CIMENTO COM COLAPSO CARDIOVASCULAR FULMINANTE - Samalyuk, Kateryna; Barbosa, Rita; Neto Cruz, Margarida; Pedreira, Joana; Gil Pereira, Margarida; Delgadinho, Isabel (Journal of the Portuguese Society of Anesthesiology, 2023)
x